2013
DOI: 10.1108/14636691311327106
|View full text |Cite
|
Sign up to set email alerts
|

One goal, different strategies: an analysis of national broadband plans in Latin America

Abstract: Purpose-The ambitious government initiatives currently underway to accelerate broadband development indicate a major shift from the consensus that prevailed during the 1990 s in the telecommunications sector. To what extent does this change represent a return to the period before market liberalization and the privatization of government-run telecom services? What are the main objectives of national broadband plans and which policy tools are best suited to achieve them? This paper aims to analyze these question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…According to Melody (2013), the regulatory instruments used have proved to be insufficient to facilitate the development of broadband infrastructures at an acceptable rate, and many countries are searching for alternative policy instruments (Falch, 2007). According to (Galperin, Mariscal, & Viecens, 2013) a similar trend can be observed in Latin America; moreover, there are states like South Korea, which show a clear preference for developmental model (Lemstra & Melody, 2014;Falch and Henten, 2010). Now, public support is seen not only as being responsible for the regulatory framework where market forces thrive, but also as the main force behind infrastructure deployment and innovative boosting measure (Feijoo Gonzalez, Gómez Barroso & Bohlin, 2011).…”
Section: Implications For the Ec Policiesmentioning
confidence: 56%
“…According to Melody (2013), the regulatory instruments used have proved to be insufficient to facilitate the development of broadband infrastructures at an acceptable rate, and many countries are searching for alternative policy instruments (Falch, 2007). According to (Galperin, Mariscal, & Viecens, 2013) a similar trend can be observed in Latin America; moreover, there are states like South Korea, which show a clear preference for developmental model (Lemstra & Melody, 2014;Falch and Henten, 2010). Now, public support is seen not only as being responsible for the regulatory framework where market forces thrive, but also as the main force behind infrastructure deployment and innovative boosting measure (Feijoo Gonzalez, Gómez Barroso & Bohlin, 2011).…”
Section: Implications For the Ec Policiesmentioning
confidence: 56%
“…Katz and Callorda (2018) state that the regulatory framework and public policies represent critical enablers of the digital ecosystem development, such as spectrum management and tax incentives. Broadband plans in Latin American countries exhibit common patterns as well as differences (Galperín et al, 2013). The main policy tools in the telecommunications sector have been public financing and investment in networks and equipment; government participation in the networks' functioning, and an active industrial policy.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Proliferation of national broadband plan is an evidence of the implementation of those policies to promote telecommunications. Galperín et al (2013) argues that broadband initiatives in Latin America mainly centre on extending coverage and enhancing competition in the wholesale segment of the network. In technologically developing nations, a competitive telecommunications sector and higher investment in ICT lead to greater broadband diffusion (Gulati and Yates, 2012, p. 749).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Other plans, represented by the US and Europe, focus on policy to create a framework for private investment with a limited range of subsidies on the supply side (Ruhle, Brusic, Kittl, & Ehrler, 2011). In the context of developing countries, studies have found that governments across the globe have, to various degrees, returned to playing a proactive role to help speed up broadband development (Calandro & Moyo, 2012;Galperin, Mariscal, & Viecens, 2013;Jain, 2014;Jayakar & Liu, 2014a;Shin & Jung, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%